An overview of conventional and non-conventional hydrogen production methods. (2021) - Kumar, Ravindra; Kumar, Anil; Pal, Amit
Abstract: H2 fuel is adopted for the upcoming generation. Leading of H2 technology is causes of decrement of fossil fuel and change of climate condition. There are multiple methods for the development of producing H2 from conventional and non-conventional resources. This paper presents the major hydrogen production technologies by the industrial and biological process and a short discussion on the present scenario and economy of H2 production and hydrogen storage. The collection of industrial techniques are involve in different kind of reforming process such as steam methane reformation (SMR), Partial oxidation (POx), auto thermal reforming (ATR) and steam iron. Biological techniques of H2 production are adopted by various developing processes such as dark-fermentation, photo fermentation, and bio-photolysis by direct and indirect method. SMR is mostly used in the industrial process and it reaches efficiency 85%. It is available nearly 50% of globally consumption. POx and ATR are also another two important processes used for industrial. The biological process is producing low yields but gaining more interest due to easy and large availability of feed materials and low pollutions. Bio-H2 production methods economy is more expensive than fossil fuel H2 production. The requirement of more research challenges the yields of bio-H2 to provide practical solutions. Several researchers have been done more works on bio-hydrogen using water and biomass along with solar energy, but still, it continues to improve the efficiency of development.